If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 13 = 62 + -10x Reorder the terms: 13 + 5x = 62 + -10x Solving 13 + 5x = 62 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 13 + 5x + 10x = 62 + -10x + 10x Combine like terms: 5x + 10x = 15x 13 + 15x = 62 + -10x + 10x Combine like terms: -10x + 10x = 0 13 + 15x = 62 + 0 13 + 15x = 62 Add '-13' to each side of the equation. 13 + -13 + 15x = 62 + -13 Combine like terms: 13 + -13 = 0 0 + 15x = 62 + -13 15x = 62 + -13 Combine like terms: 62 + -13 = 49 15x = 49 Divide each side by '15'. x = 3.266666667 Simplifying x = 3.266666667
| -a+6=a+6 | | -1x/4+4=3x/4+8 | | -t+1=6t+50 | | 7-4n=4n-41 | | 2n-8=5n-2 | | 7a+2=a+2 | | m+10=-20-2m | | -2+7m=-5m+82 | | 2x-6/3=x+7 | | 9-2x=-5x+30 | | -3-6t=7t-16 | | 3+5w=7w-5 | | w+4=7w-26 | | 6n+5=-3n+50 | | 3a-1=2a+2 | | 3m+5=6m-25 | | 9+5=-9+7x | | 4w-5=2w-15 | | 1-6w=4w+71 | | -7-4a=a+13 | | 7w-2=-6w-41 | | 6w+4=w+24 | | m+2=0-m | | h/3=9 | | x(3x+7)=0 | | -6t+2=-6+2t | | -8-2w=-4w+14 | | -2n+4=7n-77 | | -3d-5=-37-7d | | 5t+4=-116-7t | | -5d-1=-4d-7 | | 2b+7=4b+21 |